World Literature as Geoculture - D'haen, Theo (Literature and Cultural Studies E-Books Online, Collection 2026, 2026)
World Literature as Geoculture applies a geopolitical perspective to literature. It considers literature, along with all other cultural elements, as both formed by and constitutive of a region's, nation's, or continent's global position. The book opens with a chapter discussing the general relation between geopolitics and world literature. It then turns to more detailed discussions of the relations between nation and literature, European literature, comparative literature and translation, global south relations, the rise and fall of literary movements or currents as reflecting geopolitical shifts, and the position of small or minor literatures. Specific chapters focus on magical realism, Edward Said, Chinese comparative literature scholarship, and Flemish literature.